Temporal variation of ammonium in Sulfic Tropaquept cultivated with rice in experimental pots - Khairudin, Nurulhuda; Mohd Hanif, Ahmad Husni; Mohamed Zawawi, Mohamed Azwan; Zakaria, Mohamad Pauzi; Struik, Paul C.; Keesman, Karel J. (Malaysian Society of Agricultural Engineers, 2019)
Hypothetically, monitoring of soil solution NH+4-N dynamics may allow estimation of nitrogen (N) transformation rates such as the rates of nitrification, denitrification, mineralisation and immobilisation. Such observations can be used to evaluate and improve performance of N dynamics models for flooded rice systems. Therefore, the objective of this study was to evaluate temporal variation of ammonium dynamics in fertilised and flooded rice pots. Concentrations of NH+4-N were determined in soil solutions that were extracted by MacroRhizon samplers. MacroRhizon is a soil solution sampler with a pore size of 0.15 μm manufactured by Rhizosphere Research, the Netherlands. In comparison to typical soil sampling methods, some advantages of using MacroRhizon are repeated sampling at the same spot possible, easy to install and less disturbance to the soil due to the small diameter, and maximum pore size of 0.2 μm which requires no further filtering prior to chemical analysis. Results showed that under current agronomic and management practices, broadcast N application had no obvious and consistent influence on soil solution NH+4-N. Analysis of the results suggest that suitability of soil solutions extracted using the MacroRhizon samplers as alternatives for the labourious and destructive conventional soil samplings is subject to further investigation.